EFEKTIVITAS PENILAIAN KINERJA DALAM MENINGKATKAN PRODUKTIVITAS KERJA PEGAWAI KECAMATAN BENUA KAYONG KABUPATEN KETAPANG KALIMANTAN BARAT - Suryadi; Afifudin; Hayat (Halu Oleo University, 2023)
This research discusses the effectiveness of performance appraisal in increasing employee work productivity in Benua Kayong District, Ketapang Regency, West Kalimantan. This research is based on problems related to the effectiveness of performance appraisal in increasing employee work productivity. Performance appraisal is a process within an organization that aims to evaluate the performance of each individual's work. In performance appraisal, an assessment of employee cooperation with the organization can be carried out within a certain period of time. In evaluating employee performance to find out how well employees work, this study uses several data collection techniques. In this study, using qualitative research where data collection techniques were obtained through various ways including interviews, observation, documentation. The results of this study indicate that the effectiveness of performance appraisal in increasing employee work productivity is urgently needed in the sub-district of Continental Kayong, Ketapang Regency, considering that there are several factors that reduce the work productivity of these employees so that they are less effective at doing work.